2003
DOI: 10.1038/sj.bjc.6600833
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine receptor CCR2 is expressed by human multiple myeloma cells and mediates migration to bone marrow stromal cell-produced monocyte chemotactic proteins MCP-1, -2 and -3

Abstract: The restricted bone marrow (BM) localisation of multiple myeloma (MM) cells most likely results from a specific homing influenced by chemotactic factors, combined with the proper signals for growth and survival provided by the BM microenvironment. In analogy to the migration and homing of normal lymphocytes, one can hypothesise that the BM homing of MM cells is mediated by a multistep process, involving the concerted action of adhesion molecules and chemokines. In this study, we report that primary MM cells an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(39 citation statements)
references
References 31 publications
1
35
3
Order By: Relevance
“…Although the markers identified in our study have been identified previously in clinical studies of MM or its precursor states ( i.e ., MGUS and SMM),45, 46, 47, 48, 49, 50 the direction of our findings is in general opposite to observations among subjects diagnosed with MM, where higher concentrations of these markers seems to be related to generally poorer disease outcome. The reason for this difference in direction of the effect is not known but may hint toward a preclinical deregulation of these important biological systems in subjects developing MM later in life which at the time of clinical manifestation reverse in overexpression.…”
Section: Discussioncontrasting
confidence: 99%
“…Although the markers identified in our study have been identified previously in clinical studies of MM or its precursor states ( i.e ., MGUS and SMM),45, 46, 47, 48, 49, 50 the direction of our findings is in general opposite to observations among subjects diagnosed with MM, where higher concentrations of these markers seems to be related to generally poorer disease outcome. The reason for this difference in direction of the effect is not known but may hint toward a preclinical deregulation of these important biological systems in subjects developing MM later in life which at the time of clinical manifestation reverse in overexpression.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to this clear chemokinetic effect, we could not confirm previously described chemotactic effects of MCP-1 on the myeloma cell lines (Ref. 21; data not shown).…”
Section: Tnf-␣ Prestimulation Enhances Transmigration Of Myeloma Cellcontrasting
confidence: 55%
“…Autocrine chemokine-loops in myeloma cells themselves might allow the cells to interfere with the chemokine gradients presented in the microenvironment. It has been reported that bone marrow stromal cells produce MCP-1, -2, and -3 (21). Our microarray data showed that U266 did not express MCP-2 and did not regulate MCP-3 and MCP-4 in response to TNF-␣, and that only MCP-1 was under the regulation of this cytokine.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In this study, we show that SD-208 decreased IL-6 and VEGF secretion triggered by TGF-␤1 in a dose-dependent manner. SD-208 also inhibited TGF-␤1-triggered secretion of MCP-1, which binds to CCR2 on MM cells and mediates their migration to BMSCs (29), further suggesting that SD-208 decreases adhesion of MM cells to BMSCs and associated cytokine secretion.…”
Section: Discussionmentioning
confidence: 94%